2014
DOI: 10.3390/v6031294
|View full text |Cite
|
Sign up to set email alerts
|

Playing Hide and Seek: How Glycosylation of the Influenza Virus Hemagglutinin Can Modulate the Immune Response to Infection

Abstract: Seasonal influenza A viruses (IAV) originate from pandemic IAV and have undergone changes in antigenic structure, including addition of glycans to the hemagglutinin (HA) glycoprotein. The viral HA is the major target recognized by neutralizing antibodies and glycans have been proposed to shield antigenic sites on HA, thereby promoting virus survival in the face of widespread vaccination and/or infection. However, addition of glycans can also interfere with the receptor binding properties of HA and this must be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
213
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(217 citation statements)
references
References 125 publications
4
213
0
Order By: Relevance
“…It is of considerable importance to detect new antigenic changes occurring in HA protein when updating vaccine compositions. The results of our study are consistent with the results of others in terms of changes in number and location of glycosylation sites (20,21), mutations/conservation in important positions such as Q240R (22), V169T, and D239G (24,25), changes/conservation in active/binding sites (23,24), and conservation in important domains such as fusion peptide (24,25). Evaluation of changes in predicted ligandbinding sites, type and number of ligands was done in our study, which indicated a significant change in ligand binding site of 2009 isolates.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is of considerable importance to detect new antigenic changes occurring in HA protein when updating vaccine compositions. The results of our study are consistent with the results of others in terms of changes in number and location of glycosylation sites (20,21), mutations/conservation in important positions such as Q240R (22), V169T, and D239G (24,25), changes/conservation in active/binding sites (23,24), and conservation in important domains such as fusion peptide (24,25). Evaluation of changes in predicted ligandbinding sites, type and number of ligands was done in our study, which indicated a significant change in ligand binding site of 2009 isolates.…”
Section: Discussionsupporting
confidence: 93%
“…The presence of glycosylation sites, which are commonly conserved, mask the protein surface from recognition by an antibody. Addition of glycans to the HA is an important mechanism contributing to antigenic drift and therefore sustained circulation of influenza A virus in the human population (20,21). The (Table 3), in which some changes (creation/ deletion of glycosyla- Position 240, which is located in receptor binding site, is one of the important positions in HA (22).…”
Section: Resultsmentioning
confidence: 99%
“…However, the antigenic reports rely on national influenza centres' antigenic analysis that the viruses reported as like to vaccine virus were not more than fourfold different in HI titres from the vaccine or reference viruses. Further enhancement of the antigenicity and virulence of influenza virus has been attributed to shielding of the major antigenic epitopes by alteration of N-linked glycosylation sites [18]. D127E substitution seen in 6B.2 has been associated with antigenic change of other influenza viruses through modelling [17].…”
Section: Discussionmentioning
confidence: 99%
“…4 Surface glycans serve as ligands for glycan-binding proteins in cellular trafficking, adhesion and signaling events 5,6 and also mediate interactions between the vertebrate host and microbial pathogens. [7][8][9] Other processes influenced by glycan structures include innate immune signaling, autoimmune reactions and tumor metastases. 2,8 Glycan structure is determined by the concerted action of numerous genes that code for glycosyltransferases, glycosidases, and other enzymes that synthesize and remodel glycan chains, as well as accessory enzymes involved in the synthesis and transport of nucleotide sugars.…”
Section: Glycosylation As a Key Biological Processmentioning
confidence: 99%